2023
DOI: 10.1186/s13048-023-01232-z
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction of lncRNA Gm2044 and EEF2 promotes estradiol synthesis in ovarian follicular granulosa cells

Ke Hu,
Chen Wang,
Yifan Xu
et al.

Abstract: The functions and molecular mechanisms of long noncoding RNA (lncRNA) in reproduction have been widely studied at present. However, lncRNA regulating hormone synthesis in ovarian follicular granulosa cells has not been sufficiently studied. Our previous research demonstrated that lncRNA Gm2044 could promote estradiol synthesis in follicular granulosa cells. In this study, we identified 21 binding proteins of lncRNA Gm2044 in ovarian follicles using comprehensive identification of RNA-binding proteins by mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Another study focuses on a crucial yet understudied aspect of long noncoding RNA (lncRNA) function in reproductive biology – its role in regulating hormone synthesis in ovarian follicular granulosa cells [ 19 ]. By narrowing down this area of research, the study fills an important gap in our understanding of reproductive mechanisms.…”
Section: Lncrna Regulates Ovarian Physiological Functionmentioning
confidence: 99%
“…Another study focuses on a crucial yet understudied aspect of long noncoding RNA (lncRNA) function in reproductive biology – its role in regulating hormone synthesis in ovarian follicular granulosa cells [ 19 ]. By narrowing down this area of research, the study fills an important gap in our understanding of reproductive mechanisms.…”
Section: Lncrna Regulates Ovarian Physiological Functionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors found two mistakes while reading the article today. In Fig.…”
mentioning
confidence: 99%